A pathophysiological and mechanistic review of chronic inflammatory demyelinating polyradiculoneuropathy therapy - Caballero-Ávila, Marta; Martin-Aguilar, Lorena; Collet-Vidiella, Roger; Querol, Luis; Pascual-Goñi, Elba (Frontiers in Immunology, 2025)
Chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) is an immune-mediated disease of the peripheral nerves characterized by proximal and distal muscle weakness and sensory abnormalities. CIDP has been associated with various pathophysiological mechanisms that are not fully understood and that likely differ across groups of patients. It has been proposed that an interplay of different immunopathological mechanisms including the cellular, humoral and complement pathways play a key role in peripheral nerve damage in CIDP. Currently approved treatments and therapies in research often target different potential pathophysiological mechanisms. The efficacy of these different treatments can shed light on the prominence of particular pathophysiological pathways in subsets of patients with CIDP. For example, the complement pathway plays a key role in promoting macrophage-mediated demyelination, and complement inhibitors are under development as new targets in CIDP treatment, with mixed results. The neonatal Fc receptor (FcRn) has also been targeted as a promising treatment avenue due to its role in immunoglobulin G degradation. Efgartigimod is the first FcRn blocker approved for the treatment of CIDP. This review provides an overview of key proposed mechanisms of action in CIDP pathophysiology in the context of both basic scientific findings and treatment targets in recent clinical studies.